1996
DOI: 10.1542/peds.97.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Congenital Adrenal Hyperplasia: The Delfia Screening Test Overestimates Serum 17-Hydroxyprogesterone in Preterm Infants

Abstract: Objective. To compare 17-hydroxyprogesterone (17-OHP) levels measured by quantitative serum radioimmunoassay (RIA), including an extraction step, and by screening fluoroimmnoassay (FIA) on blood spots in preterm infants. Methods. Subjects were 39 healthy infants born at less than 31 weeks' gestational age. Each infant had weekly blood sampling, and RIA and FIA were performed on each sample. Results. Two hundred twenty-seven samples were taken at 28 to 41 weeks' postconceptional ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There may be additional substances in dried blood spots that interfere with immunoassays (matrix effect) (287). The DELFIA was reformulated in late 2009 to make it less sensitive to cross-reacting compounds in premature infants (288). This modification improved the positive predictive value from 0.4% to 3.7% for the first screen (249).…”
Section: B Biochemical Evaluationmentioning
confidence: 99%
“…There may be additional substances in dried blood spots that interfere with immunoassays (matrix effect) (287). The DELFIA was reformulated in late 2009 to make it less sensitive to cross-reacting compounds in premature infants (288). This modification improved the positive predictive value from 0.4% to 3.7% for the first screen (249).…”
Section: B Biochemical Evaluationmentioning
confidence: 99%
“…Moreover, the current FIA screening method looks for only the 17-OHP level, whereas with LCMS/MS we have an additional level of information for other steroid species, such as 21-DF ( 19 , 20 ). We present here a proof of concept that LC-MS/MS steroid profiling (including at least 17-OHP, 21-DF, testosterone, and D4-androstendione) may be useful for detecting not only false positive, as described elsewhere ( 9 , 10 ) but also false negative CAH cases.…”
Section: Discussionmentioning
confidence: 63%
“…In our NBS, we reported that 87.0 and 78.2% of results were false positive for the Ile-de France (IdF) region in 2019 and 2020, respectively, with positive predictive values (PPVs) of 12.0 and 16.1%, respectively. Different factors could explain such a low PPV: (i) cross-reactive detection of 17-OHP with its steroid precursors and their sulphated conjugates, which are present in the first 48 h after birth, and longer in preterm neonates ( 8 , 9 ); (ii) increased 17-OHP levels due to illness, stress, and biological variation ( 8 , 10 ); (iii) the presence of high levels of delta-5 steroids, such as pregnenolone (Preg) and 17-hydroxypregnenolone (17OHPreg) in premature newborns due to immature adrenal function. These factors make it difficult to define a predictive threshold ( 8 , 9 ) and result in anxiety for the parents during the recall process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations